2016
DOI: 10.1111/jac.12178
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Salt Tolerance of Wheat Germplasm Using a Multivariable Screening Approach

Abstract: Salinity is one of the major limitations to wheat production worldwide. This study was designed to evaluate the level of genetic variation among 150 internationally derived wheat genotypes for salinity tolerance at germination, seedling and adult plant stages, with the aim of identifying new genetic resources with desirable adaptation characteristics for breeding programmes and further genetic studies. In all the growth stages, genotype and salt treatment effects were observed. Salt stress caused 33 %, 51 % an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
159
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(175 citation statements)
references
References 36 publications
12
159
0
4
Order By: Relevance
“…Coleoptile length and root dry weight (-0.36) and shoot length and root fresh weight (-0.35) were negatively but not significantly correlated. Similar results were reported by Askari et al (2016) and Oyiga et al (2016).…”
Section: Correlation Between Characters With and Without Salt Stresssupporting
confidence: 92%
See 2 more Smart Citations
“…Coleoptile length and root dry weight (-0.36) and shoot length and root fresh weight (-0.35) were negatively but not significantly correlated. Similar results were reported by Askari et al (2016) and Oyiga et al (2016).…”
Section: Correlation Between Characters With and Without Salt Stresssupporting
confidence: 92%
“…After 4 days germination rate (%) and after 8 days germination power (%), coleoptile length (cm), shoot length (cm), root length (cm), shoot root length ratio, fresh root weight (mg), dry root weight (mg), and root fresh dry weight ratio were measured. Salt total tolerance indices based on genotype character measurements and salt rank tolerance indices based on genotype character rankings (Zencirci et al, 1990;Askari et al, 2016;Oyiga et al, 2016) were calculated and salt tolerant and susceptible wheat genotypes were determined.…”
Section: Salt Stress Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, all parameters related to the accumulation and the resulting ratios of ions, particularly Na + , K + , and Ca 2+ , could be considered as key physiological criteria for the differentiation between salt-tolerant and salt-sensitive genotypes. In most salinity studies with various crops, the salt tolerance has been found to be related to the potential of genotypes to restrict Na + influx or compartmentalize it into the vacuole, as well as permanent acquisition of K + and Ca 2+ (El-Hendawy et al, 2005a; Nawaz et al, 2010; Zhang et al, 2014; Ashraf and Ashraf, 2015; Oyiga et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…The more salt tolerant of bread wheat genotypes compared with the einkorn wheat (Aslan et al, 2015). The wheat genotypes differ from the percentage of germination and seedling characters due to different salt levels, and recorded different salt tolerance indices that discriminates tolerant and susceptible varieties effectively (Oyiga et al, 2016). The genotypes of Kırmızı Yerli, Conkesme, and Türkmen were careful drought-resistant based on two out of the three physiological parameters indices.…”
Section: Introductionmentioning
confidence: 97%